Handbook for writing and editing texts of the Faculty of tourism of the University of Maribor (University of Maribor Press, 2017)
The learning process at the faculty requires not only attending lectures and active participation in the tutorials, but also intensive individual work of a student, which is often presented in the form of a seminar paper. However, the most important individual work of a student is definitely a final paper - a diploma or a master’s thesis. In order to present and facilitate the preparation of written works for the students of the Faculty of Tourism of the University of Maribor, we have prepared this handbook for writing and editing texts at the faculty. The professional monograph covers the chapters that lead the student through the whole process of research and writing their paper. From the initial search of the research idea and the basics of scientific writing and research in tourism, to the individual steps of the research process and research methods. The professional monograph also includes a chapter on personal relationships, which in particular addresses the relationship between a student and a mentor in the process of preparing the paper or thesis. The handbook also provides practical advice on language and text designing, as well as instructions for citing references. The professional monograph, thus, combines basic information that both students of tourism and their lecturers will use in their study and work processes, as they will follow the uniform guidelines for writing texts in tourism at the Faculty of Tourism.